Polyimide fiber solid electrolyte membrane and preparation method thereof
The solid electrolyte membrane of polyimide fiber modified with metal organic frame material was prepared by coaxial electrospinning process. The core-shell structure and lithium hexafluorophosphate immersion were used to improve the conductivity and mechanical properties of lithium ions and solve the lithium ions in the prior art. The problems of low conductivity and poor mechanical properties have achieved a simple and efficient preparation method.
Patent Information
- Application Number
- CN202411260380.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyimide solid electrolyte membrane has low lithium ion conductivity, which is difficult to meet the requirements of high-performance batteries for ion conductivity. At the same time, the mechanical properties of the polyethylene oxide electrolyte membrane are poor, and the existing preparation methods are complex and costly. .
Coaxial electrospinning process is used to prepare a solid electrolyte membrane of metal organic frame material modified. It adopts a core-shell structure. The core is polyethylene oxide/metal organic frame composite fiber and the shell is polyimide/ Metal-organic frame composite fibers improve lithium ion transmission capacity through soaking of lithium hexafluorophosphate.
The mechanical strength and lithium ion transmission efficiency of the composite fiber membrane are improved, and the problems of low conductivity and poor mechanical properties of lithium ion are solved. The preparation method is simple, easy to control, and suitable for industrial production.
Smart Images

Figure CN119133591A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrolyte membranes, and in particular to a polyimide fiber solid electrolyte membrane and a preparation method thereof, which are suitable for high energy density energy storage devices of solid-state lithium-ion batteries. Background Art
[0002] Solid electrolyte membranes have gradually become a research hotspot in the battery field due to their excellent safety and energy density. Traditional liquid electrolytes have great safety risks due to leakage and flammability issues. Solid electrolyte membranes can effectively avoid these problems and improve the cycle life and working stability of batteries.
[0003] Polyimide has a wide range of application prospects in battery materials due to its excellent heat resistance, mechanical strength and chemical stability. However, the existing polyimide solid electrolyte membrane has low lithium ion conductivity and is difficult to meet the requirements of high-performance batteries for ion conductivity. Polyethylene oxide has a strong lithium ion solvation ability, but the polyethylene oxide electrolyte membrane is soft and easy to deform, and has poor mechanical properties. However, the existing polyimide electrolyte membrane is often blended with polyethylene oxide in a polar solvent and cast into a film or a spin / cast coating film forming process, which has the disadvantages of complexity and high cost. Therefore, a simple and efficient method for preparing a polyimide solid electrolyte membrane is urgently needed. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a polyimide fiber solid electrolyte membrane and a preparation method thereof. The polyimide fiber solid electrolyte membrane modified by a metal organic framework material is prepared by a coaxial electrospinning process, thereby further improving the mechanical strength and lithium ion transmission efficiency of the composite fiber membrane.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0006] A polyimide fiber solid electrolyte membrane and a preparation method thereof, characterized in that the polyimide fiber solid electrolyte membrane is a core-shell structure, the core is a polyethylene oxide / metal organic framework composite fiber; the shell is a polyimide / metal organic framework composite fiber; the average fiber diameter of the polyimide fiber solid electrolyte membrane is 200-500nm; and the membrane thickness is 30-100μm.
[0007] The above method comprises the following steps:
[0008] (1) Preparation of polyimide fiber solid electrolyte membrane: polyimide and metal organic framework material are added to N,N-dimethylformamide and mixed evenly to form a mixed solution A; polyethylene oxide and metal organic framework material are added to N,N-dimethylformamide and mixed evenly to form a mixed solution B; then the mixed solutions A and B are formed into precursor fibers by coaxial electrospinning technology, vacuum freeze-dried, rolled by a roller press, immersed in a mixed solution C of ethylene carbonate and ethyl methyl carbonate containing lithium hexafluorophosphate, and dried to obtain the polyimide fiber solid electrolyte membrane.
[0009] In the above-mentioned preparation method, preferably, in the step (1), the number average molecular weight of the polyimide is 50,000 g / mol to 150,000 g / mol; the number average molecular weight of the polyethylene oxide is 100,000 g / mol to 1,000,000 g / mol; and the metal organic framework material is one of UiO-66, MOF-177, MIL-53 (Al) and MIL-101 (Cr).
[0010] In the above preparation method, preferably, in step (1), the solid content of the polyimide solution in the mixed solution A is 3% to 20wt%; the viscosity is 1.7dL / g to 4.3dL / g; and the content of the metal organic framework material in the mixed solution A is 10% to 40wt%.
[0011] In the above preparation method, preferably, in step (1), the solid content of the polyethylene oxide solution in the mixed solution B is 1% to 15wt%; the viscosity is 0.8dL / g to 5.3dL / g; and the content of the metal organic framework material in the mixed solution B is 3% to 15wt%.
[0012] In the above-mentioned preparation method, preferably, in the step (1), during the coaxial electrospinning process, the diameters of the inner and outer needles are 0.3 to 4 mm; the flow rate ratio of the mixed solution A to the flow rate of the mixed solution B is 7:1 to 3:1; the distance between the nozzle and the collecting roller is 10 to 20 cm, and the voltage between the injection pump nozzle and the collecting roller is 15 to 30 kV.
[0013] In the above preparation method, preferably, in step (1), the vacuum freeze-drying treatment temperature is -40 to -60°C, and the treatment time is 24 to 48 hours.
[0014] In the above-mentioned preparation method, preferably, in the step (1), the roller gap pressure of the roller press is 7 to 9.5 MPa.
[0015] In the above preparation method, preferably, in step (1), the concentration of lithium hexafluorophosphate in the mixed solution C is 1-2.5 mol / L; and the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1.
[0016] Compared with the prior art, the advantages of the present invention are:
[0017] (1) The present invention adopts coaxial electrospinning technology to prepare a polyimide fiber solid electrolyte membrane modified with a metal organic framework material: the solid electrolyte membrane has a core-shell structure, the core is polyethylene oxide / metal organic framework composite fiber; the shell is polyimide / metal organic framework composite fiber; lithium hexafluorophosphate provides lithium ion concentration and migration ability, and the structure of the polyimide fiber solid electrolyte membrane is as follows Figure 1 shown.
[0018] (2) Among metal-organic framework materials, UiO-66, MOF-177, MIL-53(Al) and MIL-101(Cr) with large pore size and high specific surface area showed good lithium ion transport ability after the introduction of lithium salt.
[0019] The present invention directly adopts the coaxial electrostatic spinning process to prepare the polyimide fiber solid electrolyte membrane modified by the metal organic framework material, which not only solves the problem of poor mechanical properties of polyethylene oxide, but also solves the problem of low lithium ion conductivity of the polyimide fiber solid electrolyte membrane at room temperature. The process preparation method is simple, easy to control, and the equipment used is conventional equipment, so it is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the structure of the polyimide fiber solid electrolyte membrane prepared by the present invention.
[0021] Figure 2 This is a scanning electron microscope photograph of the polyimide fiber solid electrolyte membrane prepared in Comparative Example 1 of the present invention.
[0022] Figure 3 This is a scanning electron microscope photograph of the polyethylene oxide fiber solid electrolyte membrane prepared in Comparative Example 2 of the present invention.
[0023] Figure 4 A scanning electron microscope photograph of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane prepared in Comparative Example 4 of the present invention.
[0024] Figure 5 This is a scanning electron microscope photograph of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material UiO-66 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0027] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0028] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.
[0029] Comparative Example 1:
[0030] In order to reflect the advantages of the present invention, Comparative Example 1 is a single polyimide fiber solid electrolyte membrane, the average diameter of the polyimide fiber is 300 nm; and the thickness of the fiber membrane is 40 μm.
[0031] The preparation method of the polyimide fiber solid electrolyte membrane of this comparative example comprises the following steps:
[0032] (1) Dissolve 2 g of polyimide powder (PI, number average molecular weight 100,000 g / mol) in 18 g of N,N-dimethylformamide to prepare a 10% PI solution with a viscosity of 2.43 dL / g.
[0033] (2) The PI solution was transferred to a syringe pump for high-voltage electrospinning, wherein the diameter of the syringe pump nozzle was 1 mm, the flow rate was 1 mL / hour, the distance between the nozzle and the collecting roller was 15 cm, and the voltage between the nozzle and the collecting roller was 18 kV to obtain a fiber precursor.
[0034] (3) The fiber precursor is placed in a freeze dryer and treated at -50°C for 48 hours to obtain a dried polyimide fiber membrane.
[0035] (4) The polyimide fiber obtained in step (3) is rolled on a roller press to obtain a polyimide fiber film, and the roller gap pressure of the roller press is 9.5 MPa.
[0036] (5) The polyimide fiber membrane obtained in step (4) is immersed in a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1), and dried to obtain a polyimide fiber solid electrolyte membrane.
[0037] like Figure 1 The tensile strength of the polyimide fiber solid electrolyte membrane prepared in step (5) of the comparative example is 25.6 MPa, the Young's modulus is 2.13 GPa, and the ionic conductivity is 1.2×10 -5 ms cm -1 , the lithium ion migration number is 0.12V and the stable voltage is 4.52V.
[0038] Comparative Example 2:
[0039] In order to reflect the advantages of the present invention, Comparative Example 2 is a single polyethylene oxide fiber solid electrolyte membrane, the average diameter of the polyethylene oxide fiber is 280 nm; the fiber membrane thickness is 45 μm.
[0040] The preparation method of the polyimide fiber solid electrolyte membrane of this comparative example comprises the following steps:
[0041] (1) Dissolve 1.5 g of polyethylene oxide (PEO, number average molecular weight 400,000 g / mol) in 8.5 g of N,N-dimethylformamide to prepare a 15% PEO solution with a viscosity of 1.81 dL / g.
[0042] (2) The PI solution was transferred to a syringe pump for high-voltage electrospinning, wherein the diameter of the syringe pump nozzle was 1 mm, the flow rate was 1 mL / hour, the distance between the nozzle and the collecting roller was 15 cm, and the voltage between the nozzle and the collecting roller was 23 kV to obtain a fiber precursor.
[0043] (3) The fiber precursor is placed in a freeze dryer and treated at -50°C for 48 hours to obtain a dried polyethylene oxide fiber membrane.
[0044] (4) The polyethylene oxide fiber obtained in step (3) is rolled on a roller press to obtain a polyethylene oxide fiber membrane, and the roller gap pressure of the roller press is 9 MPa.
[0045] (5) The polyethylene oxide fiber membrane obtained in step (4) is immersed in a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1), and dried to obtain a polyethylene oxide fiber solid electrolyte membrane.
[0046] like Figure 1 The tensile strength of the polyimide fiber solid electrolyte membrane prepared in step (5) of the comparative example is 1.8 MPa, the Young's modulus is 0.16 GPa, and the ionic conductivity is 5.2×10 -5 ms cm -1 , the lithium ion migration number is 0.17V and the stable voltage is 3.73V.
[0047] Comparative Example 3:
[0048] In order to reflect the advantages of the present invention, comparative example 3 is a polyimide-coated polyethylene oxide fiber solid electrolyte membrane, the average diameter of the composite fiber is 350 nm; and the fiber membrane thickness is 50 μm.
[0049] The preparation method of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane of this comparative example comprises the following steps:
[0050] (1) 2 g of polyimide powder (PI, number average molecular weight 100000 g / mol) was dissolved in 18 g of N,N-dimethylformamide to prepare a PI solution with a mass fraction of 10% and a viscosity of 2.43 dL / g, which was mixed solution A.
[0051] (2) 1.5 g of polyethylene oxide (PEO, number average molecular weight 400,000 g / mol) was dissolved in 8.5 g of N,N-dimethylformamide to prepare a PEO solution with a mass fraction of 15% and a viscosity of 1.81 dL / g, which was mixed solution B.
[0052] (3) Connect the mixed solution A to the outer needle (diameter: 1.78 mm); connect the mixed solution B to the inner needle (diameter: 1.02 mm); push speed of solution A: 1.5 mL / hour; push speed of solution B: 0.5 mL / hour; the distance between the nozzle and the collecting roller is 15 cm, and the voltage between the nozzle and the collecting roller is 20 kV to obtain a fiber precursor.
[0053] (4) The fiber precursor is placed in a freeze dryer and treated at -50°C for 48 hours to obtain a dried polyimide-coated polyethylene oxide fiber membrane.
[0054] (5) The product obtained in step (4) is rolled on a roller press to obtain a polyimide-coated polyethylene oxide fiber membrane, and the roller gap pressure of the roller press is 8.5 MPa.
[0055] (6) The polyimide-coated polyethylene oxide fiber membrane obtained in step (5) is immersed in a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1), and dried to obtain a polyimide-coated polyethylene oxide fiber membrane solid electrolyte membrane.
[0056] like Figure 1 The tensile strength of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane prepared in step (6) of the comparative example is 28.3 MPa, the Young's modulus is 2.32 GPa, and the ionic conductivity is 4.7×10 -4 ms cm -1 , the lithium ion migration number is 0.26V and the stable voltage is 3.83V.
[0057] Embodiment 1:
[0058] In order to reflect the advantages of the present invention, Example 1 is a polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material UiO-66, the average diameter of the composite fiber is 380nm; and the fiber membrane thickness is 45μm.
[0059] The preparation method of the metal organic framework material UiO-66 modified polyimide coated polyethylene oxide fiber solid electrolyte membrane of this comparative example comprises the following steps:
[0060] (1) 2 g of polyimide powder (PI, number average molecular weight 100000 g / moL) was dissolved in 18 g of N,N-dimethylformamide to prepare a PI solution with a mass fraction of 10% and a viscosity of 2.43 dL / g; 2.22 g of metal organic framework material UiO-66 was ultrasonically dispersed into the PI solution to obtain a mixed solution A, in which the content of UiO-66 in the mixed solution A was 10%.
[0061] (2) 1.5 g of polyethylene oxide (PEO, number average molecular weight 400,000 g / moL) was dissolved in 8.5 g of N,N-dimethylformamide to prepare a PEO solution with a mass fraction of 15% and a viscosity of 1.81 dL / g; 1.76 g of the metal organic framework material UiO-66 was ultrasonically dispersed into the PEO solution to obtain a mixed solution B, in which the content of UiO-66 in the mixed solution B was 15%.
[0062] (3) Connect the mixed solution A to the outer needle (diameter: 1.78 mm); connect the mixed solution B to the inner needle (diameter: 1.02 mm); push speed of solution A: 1.5 mL / hour; push speed of solution B: 0.5 mL / hour; the distance between the nozzle and the collecting roller is 15 cm, and the voltage between the nozzle and the collecting roller is 22 kV, to obtain a fiber precursor.
[0063] (4) The fiber precursor is placed in a freeze dryer and treated at -50°C for 48 hours to obtain a polyimide-coated polyethylene oxide fiber membrane modified with the metal organic framework material UiO-66.
[0064] (5) The product obtained in step (4) is rolled on a roller press to obtain polyimide-coated polyethylene oxide fiber modified with the metal organic framework material UiO-66, and the roller gap pressure of the roller press is 8.5 MPa.
[0065] (6) The polyimide-coated polyethylene oxide fiber modified with the metal organic framework material UiO-66 obtained in step (5) is immersed in a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1), and dried to obtain the metal organic framework material UiO-66 modified polyimide-coated polyethylene oxide fiber solid electrolyte membrane.
[0066] like Figure 1 The scanning electron microscope photo of the polyimide-coated polyethylene oxide fiber modified by the metal organic framework material UiO-66 prepared in step (6) of the embodiment shows a core-shell structure with a rough surface interface. Table 1 shows the tensile strength of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material UiO-66 prepared in step (6) of the embodiment. The Young's modulus is 13.26 GPa, and the ionic conductivity is 6.54×10 -2 ms cm -1 , the lithium ion migration number is 0.72V and the stable voltage is 4.21V.
[0067] Embodiment 2:
[0068] In order to reflect the advantages of the present invention, Example 2 is a polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material MOF-177, the average diameter of the composite fiber is 420nm; and the fiber membrane thickness is 80μm.
[0069] The preparation method of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material MOF-177 of this comparative example comprises the following steps:
[0070] (1) 1.5 g of polyimide powder (PI, number average molecular weight 150000 g / moL) was dissolved in 8.5 g of N,N-dimethylformamide to prepare a PI solution with a mass fraction of 15% and a viscosity of 4.27 dL / g; 1.76 g of metal organic framework material MOF-177 was ultrasonically dispersed into the PI solution to obtain a mixed solution A, in which the content of MOF-177 in the mixed solution A was 10%.
[0071] (2) 0.5 g of polyethylene oxide (PEO, number average molecular weight 800,000 g / moL) was dissolved in 4.5 g of N,N-dimethylformamide to prepare a PEO solution with a mass fraction of 10% and a viscosity of 2.76 dL / g; 0.26 g of metal organic framework material MOF-177 was ultrasonically dispersed into the PEO solution to obtain a mixed solution B, in which the content of MOF-177 in the mixed solution B was 5%.
[0072] (3) Connect the mixed solution A to the outer needle (diameter: 2.08 mm); connect the mixed solution B to the inner needle (diameter: 1.26 mm); push speed of solution A: 0.7 mL / hour; push speed of solution B: 0.1 mL / hour; the distance between the nozzle and the collecting roller is 13 cm, and the voltage between the nozzle and the collecting roller is 28 kV to obtain a fiber precursor.
[0073] (4) The fiber precursor is placed in a freeze dryer and treated at -60°C for 36 hours to obtain a polyimide-coated polyethylene oxide fiber membrane modified with the metal organic framework material MOF-177.
[0074] (5) The product obtained in step (4) is rolled on a roller press to obtain polyimide-coated polyethylene oxide fiber modified with the metal organic framework material MOF-177, and the roller gap pressure of the roller press is 7.5 MPa.
[0075] (6) The polyimide-coated polyethylene oxide fiber modified with the metal organic framework material MOF-177 obtained in step (5) is immersed in a mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate and ethyl methyl carbonate is 1:1) in 2 mol / L lithium hexafluorophosphate, and dried to obtain a metal organic framework material MOF-177 modified polyimide-coated polyethylene oxide fiber solid electrolyte membrane.
[0076] Table 1 shows the tensile strength of the polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified with the metal organic framework material MOF-177 prepared in step (6) of the embodiment. The Young's modulus is 4.32 GPa, and the ionic conductivity is 2.12×10 -3 ms cm -1 , the lithium ion migration number is 0.59V and the stable voltage is 3.97V.
[0077] Embodiment 3:
[0078] In order to reflect the advantages of the present invention, Example 3 is a polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material MIL-53 (Al), the average diameter of the composite fiber is 500nm; and the fiber membrane thickness is 100μm.
[0079] The preparation method of the metal organic framework material MIL-53 (Al) modified polyimide coated polyethylene oxide fiber solid electrolyte membrane of this comparative example comprises the following steps:
[0080] (1) 1.5 g of polyimide powder (PI, number average molecular weight 50,000 g / moL) was dissolved in 6 g of N,N-dimethylformamide to prepare a PI solution with a mass fraction of 20% and a viscosity of 2.32 dL / g; 5 g of metal organic framework material MIL-53(Al) was ultrasonically dispersed into the PI solution to obtain a mixed solution A, in which the content of MIL-53(Al) in the mixed solution A was 40%.
[0081] (2) Dissolve 1 g of polyethylene oxide (PEO, number average molecular weight 1000000 g / moL) in 19 g of N,N-dimethylformamide to prepare a 5% PEO solution with a viscosity of 2.76 dL / g; ultrasonically disperse 1.05 g of metal organic framework material MOF-177 into the PEO solution to obtain a mixed solution B, in which the content of MIL-53(Al) in the mixed solution B is 5%.
[0082] (3) Connect the mixed solution A to the outer needle (diameter: 2.08 mm); connect the mixed solution B to the inner needle (diameter: 1.26 mm); push speed of solution A: 0.7 mL / hour; push speed of solution B: 0.35 mL / hour; the distance between the nozzle and the collecting roller is 17 cm, and the voltage between the nozzle and the collecting roller is 22 kV to obtain a fiber precursor.
[0083] (4) The fiber precursor is placed in a freeze dryer and treated at -60°C for 48 hours to obtain a polyimide-coated polyethylene oxide fiber membrane modified with the metal organic framework material MIL-53 (Al) after drying.
[0084] (5) The product obtained in step (4) is rolled on a roller press to obtain polyimide-coated polyethylene oxide fiber modified with the metal organic framework material MIL-53 (Al), and the roller gap pressure of the roller press is 7 MPa.
[0085] (6) The polyimide-coated polyethylene oxide fiber modified with the metal organic framework material MIL-53 (Al) obtained in step (5) is immersed in a 1.5 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1), and dried to obtain the metal organic framework material MIL-53 (Al) modified polyimide-coated polyethylene oxide fiber solid electrolyte membrane.
[0086] Table 1 shows the metal organic framework material MIL-53 (Al) modified polyimide coated polyethylene oxide fiber solid electrolyte membrane prepared in step (6) of the embodiment. The Young's modulus is 78.4 MPa, the ionic conductivity is 6.26 GPa, and the ionic conductivity is 7.73×10 -3 mscm -1 , the lithium ion migration number is 0.65V and the stable voltage is 4.63V.
[0087] Embodiment 4:
[0088] In order to reflect the advantages of the present invention, Example 3 is a polyimide-coated polyethylene oxide fiber solid electrolyte membrane modified by the metal organic framework material MIL-101 (Cr), the average diameter of the composite fiber is 200nm; and the fiber membrane thickness is 30μm.
[0089] The preparation method of the metal organic framework material MIL-101 (Cr) modified polyimide coated polyethylene oxide fiber solid electrolyte membrane of this comparative example comprises the following steps:
[0090] (1) Dissolve 1 g of polyimide powder (PI, number average molecular weight 50,000 g / moL) in 32.33 g of N,N-dimethylformamide to prepare a PI solution with a mass fraction of 3% and a viscosity of 1.61 dL / g; ultrasonically disperse 14.28 g of metal organic framework material MIL-101(Cr) into the PI solution to obtain a mixed solution A, in which the content of MIL-101(Cr) in the mixed solution A is 30%.
[0091] (2) Dissolve 1 g of polyethylene oxide (PEO, number average molecular weight 1000000 g / moL) in 99 g of N,N-dimethylformamide to prepare a PEO solution with a mass fraction of 1% and a viscosity of 0.81 dL / g; ultrasonically disperse 11.11 g of metal organic framework material MIL-101(Cr) into the PEO solution to obtain a mixed solution B, in which the content of MIL-101(Cr) in the mixed solution B is 10%.
[0092] (3) Connect the mixed solution A to the outer needle (diameter: 2.08 mm); connect the mixed solution B to the inner needle (diameter: 1.26 mm); push speed of solution A: 0.5 mL / hour; push speed of solution B: 0.1 mL / hour; the distance between the nozzle and the collecting roller is 20 cm, and the voltage between the nozzle and the collecting roller is 30 kV, to obtain a fiber precursor.
[0093] (4) The fiber precursor is placed in a freeze dryer and treated at -60°C for 48 hours to obtain a polyimide-coated polyethylene oxide fiber membrane modified with the metal organic framework material MIL-101 (Cr) after drying.
[0094] (5) The product obtained in step (4) is rolled on a roller press to obtain polyimide-coated polyethylene oxide fiber modified with the metal organic framework material MIL-101 (Cr), and the roller gap pressure of the roller press is 9.5 MPa.
[0095] (6) The polyimide-coated polyethylene oxide fiber modified with the metal organic framework material MIL-101 (Cr) obtained in step (5) is immersed in a mixed solution of ethylene carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate and ethyl methyl carbonate is 1:1) in 2.5 mol / L lithium hexafluorophosphate, and then dried to obtain a metal organic framework material MIL-101 (Cr) modified polyimide-coated polyethylene oxide fiber solid electrolyte membrane.
[0096] The above analysis and results prove that the use of the polyimide fiber-based solid electrolyte membrane of the present invention can effectively improve the mechanical properties, ion conductivity, lithium ion migration number and operating voltage of the solid electrolyte membrane. Table 1 Mechanical strength, Young's modulus, ionic conductivity, lithium ion transference number and linear sweep voltammetry data in comparative examples and embodiments.
Claims
1. A polyimide fiber solid electrolyte membrane and a preparation method thereof, characterized in that: The polyimide fiber solid electrolyte membrane is a core-shell structure, wherein the core is polyethylene oxide / metal organic framework composite fiber; the shell is polyimide / metal organic framework composite fiber; the average fiber diameter of the polyimide fiber solid electrolyte membrane is 200-500nm; and the membrane thickness is 30-100μm. (1) Preparation of polyimide fiber solid electrolyte membrane: polyimide and metal organic framework material are added to N,N-dimethylformamide and mixed evenly to form a mixed solution A; polyethylene oxide and metal organic framework material are added to N,N-dimethylformamide and mixed evenly to form a mixed solution B; then the mixed solutions A and B are formed into precursor fibers by coaxial electrospinning technology, vacuum freeze-dried, rolled by a roller press, immersed in a mixed solution C of ethylene carbonate and ethyl methyl carbonate containing lithium hexafluorophosphate, and dried to obtain the polyimide fiber solid electrolyte membrane.
2. The preparation method according to claim 1, characterized in that In the step (1), the number average molecular weight of polyimide is 50,000 g / mol to 150,000 g / mol; the number average molecular weight of polyethylene oxide is 100,000 g / mol to 1,000,000 g / mol; and the metal organic framework material is one of UiO-66, MOF-177, MIL-53 (Al) and MIL-101 (Cr).
3. The preparation method according to claim 1, characterized in that: In the step (1), the solid content of the polyimide solution in the mixed solution A is 3% to 20wt%; the viscosity is 1.7dL / g to 4.3dL / g; and the content of the metal organic framework material in the mixed solution A is 10% to 40wt%.
4. The preparation method according to claim 1, characterized in that: In the step (1), the solid content of the polyethylene oxide solution in the mixed solution B is 1% to 15wt%; the viscosity is 0.8dL / g to 5.3dL / g; and the content of the metal organic framework material in the mixed solution B is 3% to 15wt%.
5. The preparation method according to claim 1, characterized in that: In the step (1), during the coaxial electrospinning process, the diameters of the inner and outer needles are 0.3 to 4 mm; the flow rate ratio of the mixed solution A to the mixed solution B is 7:1 to 3:1; the distance between the nozzle and the collecting roller is 10 to 20 cm, and the voltage between the injection pump nozzle and the collecting roller is 15 to 30 kV.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In the step (1), the vacuum freeze-drying treatment temperature is -40 to -60°C, and the treatment time is 24 to 48 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (1), the roller gap pressure of the roller press is 7 to 9.5 MPa.
8. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of lithium hexafluorophosphate in the mixed solution C is 1-2.5 mol / L; and the volume ratio of ethylene carbonate to ethyl methyl carbonate is 1:1.
